2008
DOI: 10.1542/peds.2008-0412
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Morbidity by Month of Birth of Neonates Admitted to an Academic Neonatal Intensive Care Unit

Abstract: Morbidity and mortality in infants admitted to an academic NICU did not change significantly over the academic year. These observations suggest that the quality of care of critically ill neonates is not decreased early in the academic year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…New physicians begin working in the summer, and the clinical experience of these young physicians is lowest in July and August. Previous studies have suggested that the timing of birth has significant effects on the risks of perinatal and neonatal mortality, but these findings have not been consistent when comparing day versus night,114 weekday versus weekend,1,2,5,1520 and July and August versus the rest of the year 5,21,22…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…New physicians begin working in the summer, and the clinical experience of these young physicians is lowest in July and August. Previous studies have suggested that the timing of birth has significant effects on the risks of perinatal and neonatal mortality, but these findings have not been consistent when comparing day versus night,114 weekday versus weekend,1,2,5,1520 and July and August versus the rest of the year 5,21,22…”
Section: Introductionmentioning
confidence: 91%
“…Most studies have focused on overall perinatal or neonatal mortality, with few analyses of the effects of timing of birth on the mortality risk of very-low-birth-weight (VLBW) infants,1,12,21,22 the group at greatest risk of mortality. Even less is known about the impact of timing of birth on morbidity among surviving VLBW infants 12,14,22.…”
Section: Introductionmentioning
confidence: 99%
“…Newborns admitted to neonatal intensive care units (NICU), and in particular preterm newborns are at high risk for morbidity and mortality during the first week of life because of respiratory distress and bronchopulmonary dysplasia, apnea and bradycardia, necrotizing enterocolitis, intraventricular hemorrhage and periventricular leukomalacia, feeding difficulties, hypoglycemia, hyperbilirubinemia and neonatal sepsis [1]. Most of these neonatal morbidities, and in particular severe neonatal sepsis, which accounts for 11% - 27% of NICU admissions [2-4], are often associated with high mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…A reluctance to involve inexperienced trainees, such as pediatric housestaff, in medical care early in the academic year may stem from the fear that it may increase patient morbidity and mortality. This belief, sometimes called the 'July phenomenon', 7,8 exists despite evidence that morbidity and mortality remains constant over the course of the academic year, regardless of an influx of inexperienced housestaff in the summer months. 8 A number of factors may limit procedural training opportunities for pediatric housestaff.…”
Section: Discussionmentioning
confidence: 99%
“…This belief, sometimes called the 'July phenomenon', 7,8 exists despite evidence that morbidity and mortality remains constant over the course of the academic year, regardless of an influx of inexperienced housestaff in the summer months. 8 A number of factors may limit procedural training opportunities for pediatric housestaff. The increased involvement of NNPs, PAs and physician hospitalists in NICUs has decreased the proportion of patients, and thus procedures, assigned to housestaff.…”
Section: Discussionmentioning
confidence: 99%